2015
DOI: 10.1098/rsif.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Properties of neuronal facilitation that improve target tracking in natural pursuit simulations

Abstract: Although flying insects have limited visual acuity (approx. 18) and relatively small brains, many species pursue tiny targets against cluttered backgrounds with high success. Our previous computational model, inspired by electrophysiological recordings from insect 'small target motion detector' (STMD) neurons, did not account for several key properties described from the biological system. These include the recent observations of response 'facilitation' (a slow build-up of response to targets that move on long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…Currently, the neuronal circuits responsible for modulating this neuronal sensitivity and gain magnitude are unknown. Target tracking and pursuit simulations that implemented a dragonfly-inspired predictive gain modulation mechanism found that the optimal facilitation time constant should be variable, depending on the spatial statistics of a scene (Bagheri et al, 2015). In cluttered scenes, a longer time constant increases performance because of the high likelihood of temporary target occlusions; however, in more sparse scenery, a rapid facilitation time course is beneficial, as the target remains highly discriminable.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the neuronal circuits responsible for modulating this neuronal sensitivity and gain magnitude are unknown. Target tracking and pursuit simulations that implemented a dragonfly-inspired predictive gain modulation mechanism found that the optimal facilitation time constant should be variable, depending on the spatial statistics of a scene (Bagheri et al, 2015). In cluttered scenes, a longer time constant increases performance because of the high likelihood of temporary target occlusions; however, in more sparse scenery, a rapid facilitation time course is beneficial, as the target remains highly discriminable.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the ESTMD-EMD indicates that the ESTMD cascades with the EMD while the EMD-ESTMD indicates that the EMD cascades with the ESTMD. These two hybrid models have been successfully used for target tracking against cluttered backgrounds in an autonomous mobile ground robot [9,11,10]. Another directionally selective STMD model, the directionally selective small target motion detector (DSTMD in the Fig.…”
Section: Computational Models and Applicationsmentioning
confidence: 99%
“…This cumulative error usually arises from uncertainty in object location or target occlusion, with drift resulting in tracking failure. State-of-the-art trackers use techniques such as robust loss functions (Leistner et al, 2009; Masnadi-Shirazi et al, speed of pursued prey (Bagheri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%